1978
DOI: 10.1021/bi00613a013
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane movement and distribution of cholesterol in the membrane of vesicular stomatitis virus

Abstract: The transmembrane movement and distribution of cholesterol in the vesicular stomatitis virus membrane were studied by following the depletion of cholesterol from virions to interacting phospholipid vesicles and by exchange of radiolabeled cholesterol between virions and phospholipid-cholesterol vesicles. The kinetics of the cholesterol exchange or depletion reactions revealed the presence of two exponential rates: a rapid rate, dependent on the vesicle to virus ratio, and a slower rate, independent of the vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Kinetic analyses of cholesterol depletion and exchange from the VSV membrane into lipid vesicles performed in our laboratory have clearly demonstrated that VSV cholesterol is present in two distinct pools, in which we now know less than 30% resides in the inner monolayer and more than 70% in the outer monolayer (Patzer et al, 1978b); an error in the original calculations resulted in presentation in the reverse order of cholesterol bilayer distribution. Most cholesterol depletion/exchange studies done with lipid vesicles, however, suffer from a serious artifact: a considerable number of residual vesicles remain firmly adherent to the surface of the virus (or cells) following interaction with the vesicles (Moore et al, 1978;Patzer et al, 1978b). Such nonspecific adherence of lipid vesicles to VSV may affect the 1 Abbreviations used: VSV, vesicular stomatitis virus; G, glycoprotein; M, matrix protein; PC, phosphatidylcholine; PE, phosphatidylethanolamine; PS, phosphatidylserine; SPM, sphingomyelin; DPL, dipalmitoyllecithin; BSA, bovine serum albumin; PVP, polyvinylpyrrolidone); BHK, baby hamster kidney; BME, basal medium Eagle; pfu, plaque-forming units; PBS, phosphate-buffered saline; DPH, 1,6diphenyl-l,3,5-hexatriene; FCS, fetal calf serum; THF, tetrahydrofuran; HDL, high-density lipoproteins; LDL, low-density lipoproteins; DOPC, dioleoylphosphatidylcholine; DPPC, dipalmitoylphosphatidylcholine.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Kinetic analyses of cholesterol depletion and exchange from the VSV membrane into lipid vesicles performed in our laboratory have clearly demonstrated that VSV cholesterol is present in two distinct pools, in which we now know less than 30% resides in the inner monolayer and more than 70% in the outer monolayer (Patzer et al, 1978b); an error in the original calculations resulted in presentation in the reverse order of cholesterol bilayer distribution. Most cholesterol depletion/exchange studies done with lipid vesicles, however, suffer from a serious artifact: a considerable number of residual vesicles remain firmly adherent to the surface of the virus (or cells) following interaction with the vesicles (Moore et al, 1978;Patzer et al, 1978b). Such nonspecific adherence of lipid vesicles to VSV may affect the 1 Abbreviations used: VSV, vesicular stomatitis virus; G, glycoprotein; M, matrix protein; PC, phosphatidylcholine; PE, phosphatidylethanolamine; PS, phosphatidylserine; SPM, sphingomyelin; DPL, dipalmitoyllecithin; BSA, bovine serum albumin; PVP, polyvinylpyrrolidone); BHK, baby hamster kidney; BME, basal medium Eagle; pfu, plaque-forming units; PBS, phosphate-buffered saline; DPH, 1,6diphenyl-l,3,5-hexatriene; FCS, fetal calf serum; THF, tetrahydrofuran; HDL, high-density lipoproteins; LDL, low-density lipoproteins; DOPC, dioleoylphosphatidylcholine; DPPC, dipalmitoylphosphatidylcholine.…”
mentioning
confidence: 90%
“…Although exchange reactions of this type have been utilized in many instances for calculating the distribution and transbilayer movement of cholesterol, results in most cases appear to be contradictory (Poznansky & Lange, 1976;Gottlieb, 1976;Lenard & Rothman, 1976;Bloj & Zilversmit, 1977;Lange et al, 1977;Nakagawa et al, 1979;Backer & Dawidowicz, 1979; Sefton & Gaffney, 1979). Kinetic analyses of cholesterol depletion and exchange from the VSV membrane into lipid vesicles performed in our laboratory have clearly demonstrated that VSV cholesterol is present in two distinct pools, in which we now know less than 30% resides in the inner monolayer and more than 70% in the outer monolayer (Patzer et al, 1978b); an error in the original calculations resulted in presentation in the reverse order of cholesterol bilayer distribution. Most cholesterol depletion/exchange studies done with lipid vesicles, however, suffer from a serious artifact: a considerable number of residual vesicles remain firmly adherent to the surface of the virus (or cells) following interaction with the vesicles (Moore et al, 1978;Patzer et al, 1978b).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The study by Kremer et al (1977) on phospholipid transfer between model membranes supported collisionally mediated transfer. Also, a study on cholesterol transfer from vesicular stomatitis virus membranes to phospholipid vesicles (Patzer et al, 1978) as well as an investigation of cholesterol transfer from vesicles to brush border membranes (Müsch et al, 1986) suggested this mechanism.…”
mentioning
confidence: 99%
“…Evidence in favor of the collision-dependent mechanism for cholesterol exchange has been presented in several studies (Bruckdorfer & Green, 1967; Lenard & Rothman, 1976; Haran & Shporer, 1977;Poznansky & Lange, 1978;Moore et al, 1978; Patzer et al, 1978;Jonas & Maine, 1979 & Claret, 1979;Gottlieb, 1980), although in some of these the data on which the conclusions were based is somewhat scant. In addition, Bruckdorfer & Graham (1976) argued that the involvement of an aqueous cholesterol intermediate could be dismissed, because Gould et al (1955) had reported that they were unable to observe cholesterol exchange between membranes that were separated from each other by a dialysis membrane.…”
mentioning
confidence: 99%